General Physicochemical Parameters, Phenolic Composition, and Varietal Aromatic Potential of Three Red Vitis vinifera Varieties (“Merlot”, Syrah”, and “Saborinho”) Cultivated on Pico Island—Azores Archipelago - António M. Jordão; Ana C. Correia; Bárbara Martins; Ana Romão; Bruno Oliveira (International Journal of Plant Biology)
Pico Island is one of the islands of the Azores archipelago located in the North Atlantic Ocean, where there are very specific conditions for vine cultivation. In this context, there is scarce knowledge related to grape ripening under these conditions. Thus, the aim of this study was to evaluate several physicochemical parameters, the phenolic composition, antioxidant capacity, and varietal aromatic potential, of the “Merlot”, Syrah”, and “Saborinho” grape varieties cultivated on Pico Island over three vintages. The outcomes obtained demonstrated that “Merlot” grapes showed a tendency for significantly higher values of estimated alcohol degree, total phenols, flavonoid and non-flavonoid phenols, total anthocyanins, color intensity, and antioxidant capacity over the three vintages. In addition, for individual anthocyanins, “Merlot” and “Syrah” grapes showed a predominance of acetyl-anthocyanins in relation to p-coumaroylated forms, while for “Saborinho” grapes, an oppositive tendency was observed. For varietal aromatic potential, only in the 2021 vintage was it possible to detect significantly different values between the three grape varieties studied. In this case, “Merlot” and “Syrah” grapes showed the significantly highest values. Considering all parameters analyzed, the results obtained for the “Merlot” grape variety seem to show a better adaptation of this variety to the conditions of Pico Island than the remaining two varieties studied.